2004
DOI: 10.1063/1.1630306
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of line mixing in NH3 spectra. II. Effect of the perturber in infrared parallel bands

Abstract: In a previous paper [J. Chem. Phys. 116, 7544 (2002) (Paper I)] a model, based on the energy corrected sudden approximation, was proposed for the construction of the line-mixing relaxation matrix. It was successfully tested by comparisons with measured infrared spectra of ammonia-helium mixtures. The present paper extends this preliminary study by considering mixtures of NH3 with H2 and Ar. Measurements have been made at room temperature in the regions of the nu2 and nu1 bands for pressures up to several hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In other studies, it was shown that line mixing could greatly influence the values of the molecular parameters obtained during fitting processes with assumed line shapes. In fact, line mixing was also taken into accounted in several studies for the m 1 , m 2 , and m 4 bands of NH 3 perturbed by He, Ar and H 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it was shown that line mixing could greatly influence the values of the molecular parameters obtained during fitting processes with assumed line shapes. In fact, line mixing was also taken into accounted in several studies for the m 1 , m 2 , and m 4 bands of NH 3 perturbed by He, Ar and H 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hadded et al [13] have studied line mixing of 15 inversion doublets of NH 3 perturbed by He, Ar, and H 2 . More recently, these authors [14,15] have measured line mixing effects in the m 1 and m 2 bands of NH 3 at high pressure. They have demonstrated the necessity of take into account line mixing for the treatment of inversion-rotation spectra of NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to take LM into account is to build the associated relaxation matrix using the Infinite Order Sudden (IOS) approximation [1,8] or its improved Energy Corrected Sudden (ECS) extension [1,9,10]. IOS/ECS models have enabled precise modeling of LM effects for many systems and types of spectra [1], including hyperfine components due to nuclear spin [11,12] and symmetric-top spectra [13,14]. However, quite surprisingly, as shown in Ref.…”
Section: Introductionmentioning
confidence: 99%